AB5-type rare earth transition intermetallic compounds for the negative electrodes of rechargeable batteries - MA, BAO-MIN; CHEN, QUN; PENG, TZUNG-PING; LANDI, JAMES (2002)
Manganese-free rare earth-transition metal AB5-type hydrogen-absorbing alloys having favorable high rate discharge characteristics, suitable for use in rechargeable batteries for electrical vehicles or hybrid electrical vehicles, include compositions of the general formula: R(CouAlvMwNi1-u-v-w)z, where R is at least one element selected from rare earth elements and yttrium (Y), M is at least one refractory metal selected from groups IVB, VB, and VIB of the periodic table, the value of u is from 0 to about 0.25, v is from 0 to about 0.10, w is from 0 to about 0.05, and z, the ratio of R(CouAlvMwNi1-u-v-w)/R, is from about 4.70 to about 5.50. The unit cell volume is from about 87 to about 88.5 A3 at 25 DEG C, the plateau pressure is from about 3 to about 10 apsi at 25 DEG C, and the composition is essentially free of manganese.